THE SOCIAL COMPOSITION AND MAIN TASKS OF RUSSIAN RIGHT-MONARCHIST AND CENTRIST POLITICAL PARTIES OF THE EARLY TWENTIETH CENTURY - A. S. Zabolotskikh (Vestnik MGIMO-Universiteta)
This article analyzes the social composition of the political parties of the Russian Empire in the early XX century and a real reflection of interests of different social groups. The estates principle of social organization of pre-revolutionary Russia, seems, was to be decisive to formation of the party organizations. However, in practice, many public organizations (in particular, the Black Hundred Party) declared their all-estates character, trying to become the spokesman of the greatest possible number of social groups. By the beginning of XXcen tury in Russia there were about 60 parties, which could be called the all-Russian. Comparing the most famous of them, the author concludes that representatives of the Black Hundreds largely managed to realize the proclaimed all-estates construction principle of political organization. As stated by the leader of the Monarchist Party V.A.Gringmut, "Black Hundred-monarchists - are thousands, millions, it's - the whole Russian Orthodox people, remaining faithful to the oath unlimited Orthodox tsar" [10, p. 156]. The ideology of the Black Hundreds, which had the universal Christian character, reflecting the traditionalist outlook of the country's population, contributed to their penetration into the masses. Contrary to popular belief, the big bourgeoisie and the landlord class were not the only groups that are members of the «Union of October 17th». However Octobrists faced with serious problems, attracting to its ranks of workers and peasants of the Russian population, because they are more focused on employers rather than workers. For example, as the researchers note, an important role in the creation of the "Union of October 17th" played factory owners Brusnitsyns in St. Petersburg [3, p.122]. But by 1917 Octobrists altogether lost control of the labor movement. Thus, despite the constant positioning of the political parties of the Russian Empire as all-estates, in reality, they pursued the interests of certain groups of the population, which was due to the specific social and political structure of the Russian state of this epoch.